USING THE STRATEGIES OF FOREIGN COUNTRIES IN ATTRACTING FOREIGN INVESTMENTS (Marketing Journal, 2025)
The study is aimed at studying effective strategies for attracting foreign investment in Uzbekistan. The article studies modern models of attracting foreign investment and analyzes important factors affecting investment flows based on them. 627 Based on data from the World Bank, UNCTAD, IMF and OECD, global trends in foreign investment flows, the experience of major investor countries and positive changes in the economy of Uzbekistan are assessed. Based on the experience of Singapore, South Korea , China and Poland, specific strategies for attracting tax incentives, special economic zones, green investments and technological investments have been developed.
Keywords: FDI; foreign investments; investment climate; OLI Paradigm; special economic zones (SEZs); tax incentives; green investments; technological investments; sustainable economic development; Uzbekistan